Fungsi Representasi Dewan Perwakilan Daerah Republik Imdonesia Sebagai Lembaga Perwakilan Daerah - Wasti, Ryan Muthiara (UI Scholars Hub, 2017)
In the composition of the Indonesian constitution, DPD becomes a representative institution that has the duty to accommodate regional interests in political decisions. Its very important existence was not accompanied by the spirit of strict regulation in the legislation in Indonesia. This can be seen from the position and function of DPD which is weaker than the DPR. Law Number 17 of 2014 on the Composition, Status and Functions of the MPR, DPR, DPD and DPRD, which are the latest changes to the previous Susduk law, have not been able to address the need for more significant arrangements on the functions of DPD representatives themselves. This study uses normative legal methods and is carried out qualitatively (research qualitative) by analyzing legislation and other legal literature to explain the importance and significance of representative function of DPD towards the sustainability of regional progress in Indonesia.